2006
DOI: 10.1001/archinte.166.16.1739
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Levels of Tumor Necrosis Factor α and Soluble Tumor Necrosis Factor Receptors in Patients With Narcolepsy

Abstract: Narcoleptic patients show increased plasma levels of sTNF-R p75, suggesting a functional alteration of the TNF-alpha cytokine system, further corroborating a possible pathogenic role of the immune system in this sleep disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 39 publications
2
29
0
2
Order By: Relevance
“…Regarding TNF-a and IL-6, our data are consistent with previous findings by Okun et al (2004) and Vgontzas et al (1997). However, two other studies (Himmerich et al, 2006;Hinze-Selch et al, 1998) found no significant increases in TNF-a. Himmerich et al (2006) found increased sTNFR p75 levels in narcolepsy, but sTNFR p55 levels were not increased.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Regarding TNF-a and IL-6, our data are consistent with previous findings by Okun et al (2004) and Vgontzas et al (1997). However, two other studies (Himmerich et al, 2006;Hinze-Selch et al, 1998) found no significant increases in TNF-a. Himmerich et al (2006) found increased sTNFR p75 levels in narcolepsy, but sTNFR p55 levels were not increased.…”
Section: Discussionsupporting
confidence: 92%
“…However, two other studies (Himmerich et al, 2006;Hinze-Selch et al, 1998) found no significant increases in TNF-a. Himmerich et al (2006) found increased sTNFR p75 levels in narcolepsy, but sTNFR p55 levels were not increased. The most likely reasons for these inconsistencies between the studies are the very subtle changes reported and the low numbers of patients investigated.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Subjects suffering from inflammation frequently exhibit tiredness or sleepiness mediated by the increased production of proinflammatory cytokines in the setting of ‘sickness behavior', which resembles depressive symptoms [4,7]. Narcolepsy, a disorder with increased daytime sleepiness, was found to be associated with specific markers of the HLA system and increased production of proinflammatory cytokines [21,42,43]. Cytokines not only influence wakefulness regulation, but their concentrations also change depending on sleep characteristics or following sleep deprivation [44,45,46].…”
Section: Discussionmentioning
confidence: 99%
“…Somnogenic effects may be further promoted by an impact on the HPA axis, including an increase in growth hormone-releasing hormone [5,17,18,19]. States of low-grade inflammation with upregulation of cytokine signaling feature in disorders in which excessive daytime sleepiness is commonly observed, such as metabolic syndrome [20], obstructive sleep apnea and HLA-DR2-positive narcolepsy [21,22]. Cytokine levels are further related to certain habits like daily napping and the extent of physical activity [10].…”
Section: Introductionmentioning
confidence: 99%